Tumpang Tindih Sertifikat Tanah - Aziziyah, Alvina Nur; Tien Fitriyah, Mas Anienda (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
Overlapping land certificates (Overlapping) is a situation where there are land parcels that overlap with other land parcels and there are multiple certificates for the same land parcel. This study aims to determine the causes of overlapping land certificates (overlapping) both in terms of internal factors and external factors and legal remedies for settlement and future legal remedies to overcome overlapping land certificates (overlapping). This research uses empirical juridical methods or research in the field that examines the implementation or implementation of applicable legal provisions and facts that occur in society. Data collection was carried out by field studies. Data analysis was carried out using qualitative analysis methods and using a qualitative approach. The results of this study indicate that the causes of overlapping certificates (overlapping) are digitalization and also a lack of land maintenance by the community. The legal effort that can be taken to resolve the dispute is by canceling the certificate which of course has gone through several stages of the process and the future legal action is to routinely conduct outreach to certificate holders and the Ministry of Agrarian Affairs/BPN will immediately carry out electronic certificates in order to reduce overlapping land certificates (overlapping).